EOLP-03. A RETROSPECTIVE STUDY ON CAUSE OF DEATH DUE TO HIGH-GRADE GLIOMAS IN PEDIATRIC VERSUS ADULT PATIENTS. (14th November 2022) - Franson, Andrea; Junck, Larry; Lyons, Samantha
Abstract: BACKGROUND: Limited literature exists on the presumed pathophysiologic mechanisms by which children, adolescents and adults die from high-grade gliomas (HGGs). This study aims to identify the likely specific cause of death in patients with HGG based on imaging review in proximity to death. A secondary aim is to assess the use and timing of palliative care/hospice in patients with HGG. We hypothesized that most patients with HGG, both adult and pediatric, die from primary neurologic failure as a result of local tumor progression, with additional causes including hydrocephalus with subsequent brainstem herniation or causes indirectly related to tumor progression such as systemic infection. METHODS: We conducted a retrospective review of pediatric patients with WHO Grade 4 gliomas and adults with de novo Grade 3 or 4 gliomas or Grade 2 glial tumors that transformed to Grade 3/4, diagnosed from 2016 to 2021 at Michigan Medicine (IRB exemption obtained). We reviewed imaging and clinical records of patients who had brain MR and/or CT imaging within 3 - 6 weeks of death to determine a likely cause of death. RESULTS: Twenty-six pediatric patients and 43 adult patients identified met inclusion criteria. Initial analysis reveals that the majority of patients with HGG died from local tumor progression and subsequent neurologic failure. We also noted a greater use of palliative care/hospice services in pediatric patients, with less frequent referral for adult patients at any time in their disease course. Pediatric patients are almost always supported by Child and Family Life, while psychological services are rarely received by adult patients. CONCLUSIONS: Analysis is ongoing, though trends indicate that the primary cause of death in patients with HGG is through primary neurologic failure, and that there may be opportunities to lessen end-of-life suffering through patient education and the use of support services.